Hepatitis B virus regulatory HBx protein binding to DDB1 is required but is not sufficient for maximal HBV replication - Hodgson, Amanda J. (2012)
Robust hepatitis B virus (HBV) replication is stimulated by the regulatory HBx protein. HBx binds the cellular protein DDB1; however, the importance of this interaction for HBV replication remains unknown. We tested whether HBx binding to DDB1 was required for HBV replication using a plasmid based replication assay in HepG2 cells. Three DDB1 binding-deficient HBx point mutants (HBx(69), HBx(90/91), HBx(R96E)) failed to restore wildtype levels of replication from an HBx-deficient plasmid, which established the importance of the HBx-DDB1 interaction for maximal HBV replication. Analysis of overlapping HBx truncation mutants revealed that both the HBx-DDB1 binding domain and the carboxyl region are required for maximal HBV replication both in vitro and in vivo, suggesting the HBx-DDB1 interaction recruits regulatory functions critical for replication. Finally we demonstrate that HBx localizes to the Cul4A-DDB1 complex, and discuss the possible implications for models of HBV replication.